2012
DOI: 10.1371/journal.pone.0047452
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Screen for Modifiers of Ataxin-3-Derived Polyglutamine-Induced Toxicity in Drosophila

Abstract: Polyglutamine (polyQ) diseases represent a neuropathologically heterogeneous group of disorders. The common theme of these disorders is an elongated polyQ tract in otherwise unrelated proteins. So far, only symptomatic treatment can be applied to patients suffering from polyQ diseases. Despite extensive research, the molecular mechanisms underlying polyQ-induced toxicity are largely unknown. To gain insight into polyQ pathology, we performed a large-scale RNAi screen in Drosophila to identify modifiers of toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 56 publications
2
42
0
Order By: Relevance
“…In the previous section we have presented a hypothesis that might explain why enhancers of polyQ-expanded ATXN1 toxicity and aggregation are enriched in CC domains. However, there have been several screens that tested the effect of gene silencing or overexpression on the aggregation and toxicity of polyQ proteins [25][26][27]. Are the obtained results consistent with our hypothesis?…”
Section: Enhancers Of Polyq Toxicity/aggregation and CC Contentsupporting
confidence: 75%
“…In the previous section we have presented a hypothesis that might explain why enhancers of polyQ-expanded ATXN1 toxicity and aggregation are enriched in CC domains. However, there have been several screens that tested the effect of gene silencing or overexpression on the aggregation and toxicity of polyQ proteins [25][26][27]. Are the obtained results consistent with our hypothesis?…”
Section: Enhancers Of Polyq Toxicity/aggregation and CC Contentsupporting
confidence: 75%
“…Indeed, functional and/or physical interaction with polyglutamine proteins are also reported for several other shRNA target genes, such as Atf3 [59], Ddx6 [60], Fbxw8 [61], P2ry1 [62] and Map3k1 [63]. In addition, several shRNA targets found in this study are found as modifiers of toxicity in polyglutamine disease models, such as Trappc9 [34], Casp3 [64], Gnf1 ( Drosophila Rfc1) [65], and F40F8.1 ( C. elegans Cmpk1) [66]. Notably, gene expression array analysis using R6/2 HD model mice (T.Y and N.N.…”
Section: Discussionsupporting
confidence: 76%
“…The ataxia interactome that connects most of the known ataxia genes demonstrated that many ataxia-causing proteins share interacting partners, particularly among the transcription regulation, nuclear import, RNA splicing and ubiquitinylation processes [40]. These pathways have also been evidenced in genetic screens in SCA Drosophila models [178, 368-370]. The role of microRNA as potent phenotypic modulators has also been shown in fly models [92] and has been discussed in previous sections.…”
Section: Other Genetic Factorsmentioning
confidence: 99%